2021
DOI: 10.1186/s12864-021-07945-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies for canine hip dysplasia in single and multiple populations – implications and potential novel risk loci

Abstract: Background Association mapping studies of quantitative trait loci (QTL) for canine hip dysplasia (CHD) can contribute to the understanding of the genetic background of this common and debilitating disease and might contribute to its genetic improvement. The power of association studies for CHD is limited by relatively small sample numbers for CHD records within countries, suggesting potential benefits of joining data across countries. However, this is complicated due to the use of different sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Among British-, Finnish-, and Swedish-based German shepherd dogs, CHD was studied within single geography-restricted populations as well as by meta-analysis. Although five associations were identified, including those within proximity to genes MED13 and PLEKHA7 (115), none of the associated loci overlapped between single populations (116). Further discordance among genetic association studies is documented (114)(115)(116)(117)(118)(119)(120)(121)(122).…”
Section: Truly Complex Diseasesmentioning
confidence: 97%
See 1 more Smart Citation
“…Among British-, Finnish-, and Swedish-based German shepherd dogs, CHD was studied within single geography-restricted populations as well as by meta-analysis. Although five associations were identified, including those within proximity to genes MED13 and PLEKHA7 (115), none of the associated loci overlapped between single populations (116). Further discordance among genetic association studies is documented (114)(115)(116)(117)(118)(119)(120)(121)(122).…”
Section: Truly Complex Diseasesmentioning
confidence: 97%
“…Although five associations were identified, including those within proximity to genes MED13 and PLEKHA7 (115), none of the associated loci overlapped between single populations (116). Further discordance among genetic association studies is documented (114)(115)(116)(117)(118)(119)(120)(121)(122). Discrepancies between association studies have led to the view that CHD is strongly influenced by the genomic architectures of affected populations, though surely other confounding variables, such as CHD screening methodology, age, neuter status, and obesity, could be at play.…”
Section: Truly Complex Diseasesmentioning
confidence: 99%
“…This has led to more sublime patient qualification criteria for surgery and also to a lower rate of complication rates as a result (35). The genetic background has recently been widely investigated and the latest data strongly indicates the complex genetic nature of hip dysplasia in dogs, with multiple loci being associated with the trait, most of which are population-specific (41). There are also substantial signs that indicate the existence of partially distinct loci and genes or pathways in the development of incongruity, mild dysplasia, moderateto-severe dysplasia and osteoarthritis of the canine hip Pelvic osteotomy techniques in the management of canine hip dysplasia -evolution of the treatment paradigm joints (22,23,41).…”
Section: Causes and Pathogenesismentioning
confidence: 99%
“…The genetic background has recently been widely investigated and the latest data strongly indicates the complex genetic nature of hip dysplasia in dogs, with multiple loci being associated with the trait, most of which are population-specific (41). There are also substantial signs that indicate the existence of partially distinct loci and genes or pathways in the development of incongruity, mild dysplasia, moderateto-severe dysplasia and osteoarthritis of the canine hip Pelvic osteotomy techniques in the management of canine hip dysplasia -evolution of the treatment paradigm joints (22,23,41). The fundamental stabilizer of the coxofemoral joint consists of the ligament of the head of the femur, the joint capsule and the dorsal acetabular rim (DAR).…”
Section: Causes and Pathogenesismentioning
confidence: 99%
“…The pathogenesis of dog OA closely resembles the primary disease in humans [ 11 ], despite many questions remaining unanswered regarding this poorly understood entity [ 9 , 10 ]. Some genome-wide association studies in dogs identified single nucleotide polymorphisms that were linked with canine HD [ 12 , 13 ] and the intronic deletion in the fibrillin-2 gene in the fibrous joint capsule was associated with canine hip laxity [ 13 ]. Similar studies were performed in humans and several genes were found to be related to HD development, such as CX3CR1 [ 14 ], GDF5 [ 15 ] and CTBP2 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%